2018
DOI: 10.1210/jc.2017-02498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Glucose Monitoring on Glycemic Control, Acute Admissions, and Quality of Life: A Real-World Study

Abstract: Sensor-augmented pump therapy in patients with T1D followed in specialized centers improves HbA1c, fear of hypoglycemia, and QOL, whereas work absenteeism and admissions for acute diabetes complications decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 26 publications
6
127
1
5
Order By: Relevance
“…In addition, hypoglycemia prevention is beneficial in young children with liver GSDs who are on overnight tube feeds; CGMS alarms can alert parents/caregivers to impending hypoglycemia and subsequently take corrective actions such as supplementary feeds or check for tube displacement or kinking. CGMS also leads to overall improvements in patients' perceptions about quality of life, as reported by patients #2 and #3 above and established in literature (Charleer et al 2018;Polonsky and Hessler 2013).…”
Section: Discussionsupporting
confidence: 62%
“…In addition, hypoglycemia prevention is beneficial in young children with liver GSDs who are on overnight tube feeds; CGMS alarms can alert parents/caregivers to impending hypoglycemia and subsequently take corrective actions such as supplementary feeds or check for tube displacement or kinking. CGMS also leads to overall improvements in patients' perceptions about quality of life, as reported by patients #2 and #3 above and established in literature (Charleer et al 2018;Polonsky and Hessler 2013).…”
Section: Discussionsupporting
confidence: 62%
“…Taking into account a mean Belgian cost of V4,733 per hospitalization for hypoglycemia or ketoacidosis (3), the Belgian health care provider could save V151,456 of direct costs in the first year of isCGM reimbursement. However, the magnitude is much lower, which could be explained by low baseline incidence of diabetes-related admissions in the current cohort (3.3%) compared with the high incidence (16%) in the CGM trial, in which people were mainly selected on the basis of problematic hypoglycemia (3).…”
Section: Discussionmentioning
confidence: 72%
“…Since the introduction of continuous glucose monitoring (CGM), the daily burden of multiple daily finger-stick tests and the need to constantly carry a blood glucose meter, test strips, lancets, and blood glucose logbooks have been reduced. Moreover, favorable results on hypoglycemia risk, quality of life, and hospitalization rate have been reported (3)(4)(5)(6). However, widespread use of CGM has been hampered by high costs and lack of reimbursement (7), relatively short sensor lifetime, and need for daily calibration (8).…”
mentioning
confidence: 99%
“…31 Real-world use of CGM in a prospective observational trial of type 1 diabetes showed an almost 75% reduction in hospitalization for hypoglycemia and a reduction of 68% in days of hospitalization per 100 patient-years. 32 Results in type 2 diabetes are less dramatic, due to the decreased frequency of hypoglycemia.…”
Section: S2-50mentioning
confidence: 99%